Psychological aspects of the translation of colloquial and everyday vocabulary - Ernest E. Ivashkevych (Психолінгвістика, 2017)
In this article there were shown psychological aspects of the translation of colloquial and everyday vocabulary using the example of the novel “The Catcher in the Rye” by Jerome David Salinger. It was proved that English translation would be a complete replacement of the original and communicative interpreter’s identification in the original text according to functional, structural and semantic plans. In the article there were shown several types of identification.